A carbon capture and storage technique using gold nanoparticles coupled with Cu-based composited thin film catalysts. Issue 20 (26th September 2022) - Kaoru, Onuma; Huang, Yan-Jia; Yen, Zhi-long; Kaun, Chao-Cheng; Hsieh, Ya-Ping; Su, Yen-Hsun
Abstract : Scheme and band diagram for Au NPs combined with a Cu x O thin film are synthesized by a self-assembly process and electrochemical modification. Au/Cu x O for developing carbon capture and storage performance. Abstract : Greenhouse-gas emissions and energy shortages are critical problems that need to be solved. Developing novel catalytic materials that can reduce greenhouse gases such as carbon dioxide and convert them to fuels is a viable way forward. In this work, we synthesize a composite photocatalytic material of gold nanoparticles (Au NPs) and cuprous oxide (Cu2 O) for the cathode electrode to satisfy carbon capture and storage (CCS). The surface plasmon resonance (SPR) of the 15 nanometer Au NPs is observed for optical properties and the absorption peak wavelength is about 530 nanometers in the visible light range. The electrodeposited Cu2 O thin film shows a cubic structure and Cu(i ) oxidation state by X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS), respectively. The combination process of Au NPs and the Cu2 O thin film is accelerated through the self-assembly method. Interestingly, the oxidation state of copper transfers from Cu(i ) to Cu(ii ) after the electrochemical modification. The oxidation transition forms a CuO/Cu2 O thin film which has potential in CCS and the CO2 RR. During the reaction, the pH value changes from 6.77 to 8.29, inferring that the Au/Cu2 O thin film captured CO2 from air to form bicarbonate and carbonate in the solution. The amount of bicarbonate and carbonate in the solution after 60 minutes is 35-fold higher than that before the reaction. This discovery supports its outstanding catalytic ability for not only CCS but also the CO2 RR. Moreover, the theoretical results demonstrated that the electric field enhancement between the Au NPs, Cu2 O and the hot electron effect is uncovered using finite-difference time-domain simulation. Density functional theory (DFT) calculations suggest that the CuO (0 1 1) surface is active for reactions, confirmed by the HR-TEM image. Our study unveils the possibility of CCS enhancement by using the surface plasmon resonance (SPR) of Au NPs and the electrochemical modification of Cu-based materials.